Crystal growth, crystal structure and optical properties of calcium antimony tartrate nonahydrate, Ca[Sb2((+)C4H2O6)2]·9H2O. Issue 12 (18th November 2015) - Bohatý, Ladislav; Held, Peter; Becker, Petra
Abstract : Large single crystals of the non‐centrosymmetric orthorhombic calcium antimony tartrate nonahydrate have been grown from aqueous solutions. The refractive indices of the crystals and their dispersion grant access to phase matched collinear second harmonic generation of both, type I and type II processes in a broad wavelength range. Abstract : Large single crystals of optical quality of the non‐centrosymmetric orthorhombic (space group P 21 21 21 ) calcium antimony tartrate nonahydrate, Ca[Sb2 ((+) C4 H2 O6 )2 ]·9H2 O, were grown from aqueous solution. The crystal structure and thermal stability of the crystals are evaluated and refractive indices and their dispersion in the wavelength range 404 nm – 1083 nm are reported. Based on the linear optical data phase matching conditions for second harmonic generation (SHG) are analysed. This new non‐centrosymmetric crystal allows phase matched collinear SHG processes of both, type I and type II, in a broad wavelength range in the visible and near IR regions.